Level kemampuan metakognitif siswa dalam pembelajaran matematika berdasarkan gaya kognitif - Nur Eva Zakiah (Program Studi Pendidikan Matematika Program Pascasarjan Universitas Negeri Yogyakarta, 2020)
Tujuan penelitian adalah untuk mendeskripsikan level kemampuan metakognitif siswa berdasarkan gaya kognitif (Field Dependent or FD dan Field Independent or FI). Subjek penelitian adalah siswa kelas X (n = 33) salah satu SMA Negeri di Kabupaten Ciamis Provinsi Jawa Barat. Selanjutnya subjek dikelompokkan berdasarkan kategori Kemampuan Awal Matematis (KAM) (tinggi, sedang, dan rendah). Penelitian ini merupakan penelitian deskriptif menggunakan pendekatan kuantitatif dan kualitatif. Pengumpulan data menggunakan tes untuk menentukan level kemampuan metakognitif siswa dan Group Embedded Figure Test (GEFT) untuk mengklasifikasikan gaya kognitif siswa. Hasil penelitian menunjukkan bahwa: (1) level kemampuan metakognitif siswa dengan KAM tinggi untuk gaya belajar FD dan FI adalah reflective use; (2) level kemampuan metakognitif siswa dengan KAM sedang dengan gaya kognitif FD adalah strategic use, sedangkan FI adalah reflective use; dan (3) level kemampuan metakognitif siswa dengan KAM rendah dengan gaya kognitif FD adalah aware use, sedangkan FI adalah strategic use. The level of students' metacognitive ability in learning mathematics based on cognitive stylesAbstractThe research objective was to describe the level of students’ metacognitive ability based on cognitive style (Field Dependent or FD and Field Independent or FI). The research subjects were tenth-grade students (n = 33) at a public senior high school in Ciamis Regency, West Java Province. Furthermore, the subjects were grouped based on the Initial Mathematical Ability (IMA) category (high, medium, and low). This research was a descriptive study using quantitative and qualitative approaches. Data collection used a test to determine the level of students’ metacognitive ability and the Group Embedded Figure Test (GEFT) to classify students’ cognitive styles. The results showed that: (1) the level of students’ metacognitive ability with high category of IMA for the cognitive style of FD and FI was reflective use; (2) the level of students’ metacognitive ability with medium category of IMA for the cognitive style of FD was strategic use, while FI was reflective use; and (3) the level of students’ metacognitive ability with low category of IMA for the cognitive style of FD was aware use, while FI was strategic use.